O desenvolvimento da capacidade inovativa: um estudo em uma organização do segmento atacadista distribuidor - Moraes, Priscila Sampaio de (2021)
In competitive markets, organizational resources provide companies with a higher level of performance and prominence. The Wholesaler-Distributor sector is an important link between industries and customers (retailers), inserted in a dynamic environment marked by global growth. In this context, this study aims to analyze the organizational instruments and mechanisms responsible for the development of Innovative Capacity in an organization in the Wholesaler-Distributor segment. To identify how the development of innovative capacity occurs in the company under study, the organizational elements and mechanisms proposed by Meirelles and Camargo (2014) and the model by Wang and Ahmed (2007) were used to analyze the set of innovative capacity. Based on this, this research is characterized as a single case study with a qualitative approach. The main results of the study show that in relation to the identification of innovation typologies, it was found that the company has service innovation, process innovation, market innovation, strategic innovation and behavioral innovation. The most predominant innovations according to the statements of the managers interviewed were considered for analysis, namely: service innovation, process innovation and behavioral innovation. The typologies of service, process and behavioral innovation are supported by mechanisms and instruments for developing innovative capacity that occurs through behaviors and skills of change and innovation, routines and processes of search and innovation and mechanisms of learning and knowledge governance.